Pembuatan Sabun Cuci Piring (PSCP) dari Bahan Alami di Desa Cinta Rakyat Percut Sei.Tuan - Alya Rosandiyus Putri; Siti Aisyah Tanjung; Muhammad Bagas; Triand Ester DP Sitohang; Heni Prastika; Ola Syahira; Putri Sofia Ardhana (Jurnal Pengabdian Masyarakat, 2024)
Soap is one of the cleaning tools that exist in everyday life. One type of soap is  dishwashing soap.  Dish washing soap can remove dirt and oil on food utensils such as plates, cutlery and so on. The aim of this trainingin making dishwashing soap from natural ingredients is to improve people’s skills and knowledge. With this training, people can make their own dishwashing soap because it uses natural ingredients and does not require expensive costs. The benefits  of this training are useful for the community o that they can become entrepreneurs to increase economic value and change broader mindsets regarding the importance of the benefits of natural materials. This training was carried out in Cinta Rakyat Village, Percut Sei.Tuan District, Deli Serdang Regency, North Sumatera on 25 Nevember-28 November 2023. Training activities were carried out using descriptive, discussion, questin, and answer and meaning-making  methods. The results of training evaluations carried out after the activities have met satisfaction index and the development of training activities  can be carried out routinely by.